2017
DOI: 10.1016/j.ihj.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in epidemiology of dyslipidemias in India

Abstract: Dyslipidemia is the most important atherosclerotic risk factor. Review of population based studies in India shows increasing mean total cholesterol levels. Recent studies have reported that high cholesterol is present in 25-30% of urban and 15-20% rural subjects. This prevalence is lower than high-income countries. The most common dyslipidemia in India are borderline high LDL cholesterol, low HDL cholesterol and high triglycerides. Studies have reported that over a 20-year period total cholesterol, LDL cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 55 publications
0
99
1
7
Order By: Relevance
“…Overall, an alarming 53.24% of the population had a cholesterol levels above 200 mg/dL, and thus can be considered hypercholesterolemic. [22] Importantly, cholesterol levels of the study participants were found to conform to a normal distribution with a mean of 208.5 ± 49.9 mg/dL, and a range of 110.4 mg/dL to 306.2 mg/dL [ Figure 1]. Conformity of the distribution was tested by classical statistical analysis of the variance (q 2 ) with confidence Table 2 also shows that the mean levels of cholesterol and HDL-C did not significantly differ between both genders.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, an alarming 53.24% of the population had a cholesterol levels above 200 mg/dL, and thus can be considered hypercholesterolemic. [22] Importantly, cholesterol levels of the study participants were found to conform to a normal distribution with a mean of 208.5 ± 49.9 mg/dL, and a range of 110.4 mg/dL to 306.2 mg/dL [ Figure 1]. Conformity of the distribution was tested by classical statistical analysis of the variance (q 2 ) with confidence Table 2 also shows that the mean levels of cholesterol and HDL-C did not significantly differ between both genders.…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter High LDL C, low HDL-C, and high TGs are the most common type of dyslipidemia in India [3]. Trend analysis of over two decades using data of two representative cross-sectional surveys conducted among men and women aged 35-64 years, residing in urban and rural areas (survey 1 [1991][1992][1993][1994], and survey 2 [2010][2011][2012]) in the National Capital Region of Delhi indicated that rapid rise in the burden of risk factors such as overweight, raised blood pressure, and raised blood glucose [12].…”
Section: Discussionmentioning
confidence: 99%
“…Trend analysis of dyslipidemia in India revealed that over a 20-year period TC, low-density lipoproteincholesterol (LDL-C), and triglyceride (TG) levels have increased among urban population in India [3]. A recent survey of the National Nutrition Monitoring Bureau Survey indicated an overall prevalence of hypertension among urban adult men and women in selected states of India as 31% and 26%, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia is a well-established risk factor of CVD amounting to more than half of the global cases of coronary artery disease [2,3]. Its prevalence has increased over a period of 20 years among the urban population in India [4]. Rapid urbanization, rural-tourban migration, poor dietary habits, physical inactivity, sociocultural factors, and genetic predisposition all contribute to dyslipidemia [5].…”
Section: Introductionmentioning
confidence: 99%